2019
DOI: 10.1609/aaai.v33i01.33015281
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach to Informative Feature Extraction from Multimodal Data

Abstract: One primary focus in multimodal feature extraction is to find the representations of individual modalities that are maximally correlated. As a well-known measure of dependence, the Hirschfeld-Gebelein-Rényi (HGR) maximal correlation becomes an appealing objective because of its operational meaning and desirable properties. However, the strict whitening constraints formalized in the HGR maximal correlation limit its application. To address this problem, this paper proposes Soft-HGR, a novel framework to extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Proof: See Appendix B. Note that the H-score can be efficiently estimated from data samples, via, e.g., [10,Algorithm 1]. Then, we can set the negative H-score −H (f θ , g) as our loss function, and use SGD to train the optimal parameters θ H and g H .…”
Section: B Mcr With Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof: See Appendix B. Note that the H-score can be efficiently estimated from data samples, via, e.g., [10,Algorithm 1]. Then, we can set the negative H-score −H (f θ , g) as our loss function, and use SGD to train the optimal parameters θ H and g H .…”
Section: B Mcr With Deep Learningmentioning
confidence: 99%
“…is a normalized measure of the dependence between two random variables in the k-dimensional functional spaces. In particular, the functions f and g that achieve the maximum value of (17), called maximal correlation functions, have been shown to take important roles in information theory [11], [15] and machine learning [10], [16].…”
Section: Relation To Hgr Maximal Correlationmentioning
confidence: 99%
“…However, these good detection capabilities come with the drawback of high computational requirements. Many different approaches have been proposed in the state of the art to decrease the computational requirements by means of input dimensional reduction [41,42]. The proposed approach follows these main guidelines, but it makes use of a low dimensonality input (80×60 pixels) to avoid high computational requirements.…”
Section: Manhole Detectionmentioning
confidence: 99%
“…Therefore, from (22) and (16), the characterization of the sample complexity (7) can be reduced to the minimization of Γ XY 2 F subjected to (11) and (23). Since (23) is a quadratic function of Γ XY , this is equivalent to the optimization problem:…”
Section: A the Sample Complexity For The Case σ K > σ K+1mentioning
confidence: 99%
“…In machine learning problems, the variable Y can be viewed as the label, and X is the data variable that is used to infer or predict about attributes of Y . It can be shown that the optimal functions f * , g * maximizing (1), called the maximal correlation functions, extract the most correlated aspects between X, Y , which take important roles in statistics [7], [8], information theory [6], [9], machine learning [10], [11], and recently in interpreting deep neural networks [12]. Therefore, efficiently and effectively computing maximal correlation functions from data appears to be important in information theory and machine learning.…”
Section: Introductionmentioning
confidence: 99%